ENC1 Facilitates Colorectal Carcinoma Tumorigenesis and Metastasis via JAK2/STAT5/AKT Axis-Mediated Epithelial Mesenchymal Transition and Stemness - Cui, Ying; Yang, Jiani; Bai, Yibing; Li, QingWei; Yao, Yuanfei; Liu, Chao; Wu, Feng; Zhang, Jingchun; Zhang, Yanqiao (Frontiers in Cell and Developmental Biology, 2021)
Ectodermal neural cortex 1 (ENC1) is an actin binding protein and has been known to be upregulated in several cancers, but the molecular mechanisms through which it contributes to the pathology of CRC has largely been elusive. We utilized data mining and validated the aberrant expression of ENC1. Following which phenotypic traits of malignancy were assessed in vitro. Ruxolitinib, was used as a surrogate to compare the effects of ENC1 expression and silencing on JAK-STAT-AKT pathway. In vivo models were employed to confirm the in vitro observations. Computations analysis, strengthened by in-situ and in vitro data confirmed over expression of ENC1 in CRC and predicted a poor prognosis. While enhanced cell proliferation, invasion, migration, EMT and stemness were associated with ENC1 overexpression. Silencing of ENC1 down regulated the phenotypes. Additionally, silencing of ENC1 significantly reduced activation of JAK2 and consequent activation of STAT5 and AKT comparable to Ruxolitinib inhibition of JAK2. Silencing of ENC1, resulted in lesser tumor volumes and fewer numbers of tumors, in vivo. These data suggest that ENC1 induces CRC through the JAK2-STAT5-AKT axis. ENC1 is a suitable diagnostic marker for CRC detection and ENC1 targeting therapies may suppress CRC progression.